2011
DOI: 10.1111/j.1471-4159.2011.07410.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic olanzapine treatment decreases arachidonic acid turnover and prostaglandin E2 concentration in rat brain

Abstract: Olanzapine (OLZ) is used to treat bipolar disorder, but its therapeutic mechanism of action is not clear. Arachidonic acid (AA, 20:4n-6) plays a critical role in brain signaling and an upregulated AA metabolic cascade was reported in postmortem brains from bipolar disorder patients. Here we tested whether, similar to the action of the mood stabilizers lithium, carbamazepine and valproate, chronic OLZ treatment would reduce AA turnover in rat brain. We administered OLZ (6 mg/kg/day) or vehicle i.p. to male rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 85 publications
(174 reference statements)
2
45
1
3
Order By: Relevance
“…At present, not much is known about this fatty acid in relation to the pathology of psychosis, and studies are therefore required. Antipsychotic medication has been shown to exert effects on PUFA metabolism in animal studies (Cheon et al, 2011;Modi et al, 2013), an observational study (Khan et al, 2002), and a clinical study (Evans et al, 2003). In the latter it was demonstrated that 6 months of antipsychotic treatment in first-episode psychotic patients normalized peripheral DHA levels.…”
Section: Discussionmentioning
confidence: 98%
“…At present, not much is known about this fatty acid in relation to the pathology of psychosis, and studies are therefore required. Antipsychotic medication has been shown to exert effects on PUFA metabolism in animal studies (Cheon et al, 2011;Modi et al, 2013), an observational study (Khan et al, 2002), and a clinical study (Evans et al, 2003). In the latter it was demonstrated that 6 months of antipsychotic treatment in first-episode psychotic patients normalized peripheral DHA levels.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are in line with previous reports in which OLZ was found to exert both anti-and pro-inflammatory effects. 10,26,32,[38][39][40]73 In this study we used two concentrations of OLZ: 1 and 50 mM. Unlike most of the drugs used for prophylactic treatment in schizophrenia and bipolar disorder, OLZ is a drug whose plasma concentration is not routinely monitored in treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Verbal memory was investigated using the Rey Auditory Verbal Learning Test (RAVLT) [38,39], assessing total recall across five learning trials, immediate recall following a distractor list, 30-min delayed recall and recognition. Executive function was assessed with the Trail Making Test (TMT) part B, the Wechsler Adult Intelligence Scale-III (WAIS-III) letter-number sequencing test [40], the Repeatable Battery of the Assessment of Neuropsychological Status (RBANS) digit span test [41] and the Spatial Working Memory (SWM) from the Cambridge Neuropsychological Test Automated Battery (CANTAB; using the variables ‘between-search errors' and ‘strategy').…”
Section: Methodsmentioning
confidence: 99%